Comparison of Synechiae Formation in patients undergoing Endoscopic Sinus Surgery with and without using Silastic Splints - Saifullah Khan, Saira Zaman, Athar Adnan Uppal, Ayesha Shahbaz, Sadia Iram, Syed Abdullah Hyder, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Endoscopic sinus surgery (ESS) is a surgical procedure used to remove blockages in the sinuses. These blockages are caused by various nasal diseases like recalcitrant chronic rhinosinusitis, Nasal polyposis, and Concha bullosa. These problems can cause sinusitis, resulting in nasal blockage. Treatment of these conditions can either be medical or surgical. Synechiae are a frequent complication following endoscopic sinus surgery (ESS). Despite their prevalence, the actual clinical significance of synechiae formation after ESS remains understudied. Objective: To observe the formation of synechiae formation in patients undergoing endoscopic sinus surgery with and without silastic splints. Study Design: Comparative study. Place and Duration of Study: Department of ENT Head and Neck Surgery, KRL Hospital, Islamabad from 1st May 2015 to 1st October 2015. Methods: 60 patients were divided randomly into two groups, Group A and Group B. Endoscopic sinus surgery was performed on all these patients, and silastic splints were used in Group A after surgery. In Group B only meticulous care was done post-operatively. Adhesion formation was observed in these patients in 4 weeks post-operatively. Results: The age bracket was 15 to 45 years. The mean age was 31.1±7.97 years in group A and 31.4±8.76 years in group B. The male patients were 16 (53.3%) in group A and 14(46.7%) patients were female. Eighteen (60%) patients in group B were male and 12 (40%) patients were female in group B. In the comparison of postoperative synechiae formation in both groups, there was no statistical difference between both groups after 4 weeks postoperatively. Conclusion: Endoscopic sinus surgery substantially improves the symptoms of patients suffering from chronic rhinosinusitis, nasal polyps, and concha bullosa, and a definitive decrease in antibiotic and antihistamine requirement. However, no significant difference in synechiae formation between groups was found within 4 weeks postoperatively. Keywords: Synechiae formation, Endoscopic sinus surgery, Silastic splints.